The Relation of Metaphisics to Political Theory in the Thoungt of al-Fārābī - Nanang Tahqiq (Refleksi, 1999)
This paper is a summary of al-Fārābī's political theory. His book Ara' Ahl al-Madina al-Fadhila edited by Nader and translated and also edited by Walzer is the only book this paper focuses on. However, other books or sources are quoted as far as is necessary.